Unmet Supportive Care Needs of Lung Cancer Survival Patients at Different Cancer Stages and Treatment Phases - Lee PY; Chen YA; Tsai TH; Chen CY; Shieh SH (Journal of Multidisciplinary Healthcare)
Pei-Yi Lee,1,2 Yu-An Chen,3 Tung-Han Tsai,4 Chih-Yi Chen,5,6,* Shwn-Huey Shieh4,7,* 1Department of Public Health, China Medical University, Taichung, 406040, Taiwan; 2Department of Gerontological Health Care, Central Taiwan University of Science and Technology (CTUST), Taichung, 40601, Taiwan; 3Department of Education, Taichung Veterans General Hospital, Taichung, 40705, Taiwan; 4Department of Health Services Administration, China Medical University, Taichung, 406040, Taiwan; 5Institute of Medicine Chung Shan Medical University, Taichung, 40201, Taiwan; 6Division of Thoracic Surgery, Department of Surgery, Chung Shan Medical University Hospital, Taichung, 40201, Taiwan; 7Department of Nursing, China Medical University, Taichung, 406040, Taiwan*These authors contributed equally to this workCorrespondence: Shwn-Huey Shieh, Department of Health Services Administration, China Medical University, No. 100, Section 1, Jingmao Road, Beitun District, Taichung City, 406040, Taiwan, Email shshieh@mail.cmu.edu.tw Chih-Yi Chen, Institute of Medicine Chung Shan Medical University, No. 110, Section 1, Jianguo North Road, Taichung City, 40201, Taiwan, Email cshy1566@csh.org.twPurpose: This study examined the unmet supportive care needs of lung cancer patients across different cancer stages and treatment phases, as well as the factors associated with these unmet needs.Patients and methods: Data from 501 lung cancer patients at a cancer center in central Taiwan were analyzed to assess their unmet supportive care needs across dimensions such as health information, patient care, treatment, nutrition, psychosocial, and economic needs. Associations with sex, age, cancer stage, and treatment phase were investigated.Results: Compared with male patients, female patients exhibited fewer unmet health information needs (aOR=0.40; p=0.021). Older patients had greater patient care needs than younger patients did (aOR=3.08, p=0.026). Patients in the in-treatment (p< 0.001) and follow-up (p=0.025) phases exhibited significantly lower needs for health information than did those in the newly diagnosed phase. Similarly, patients in the treatment (aOR=0.42, p=0.006), recurrence (aOR=0.24, p=0.043), and follow-up (aOR=0.12, p=0.007) phases exhibited significantly lower needs for patient care than did those in the newly diagnosed phase. Regarding treatment needs, patients in the treatment phase also demonstrated lower needs than did those in the newly diagnosed phase (aOR=0.12, p=0.004). Patients in the treatment phase had lower nutritional needs than did those in the newly diagnosed phase (aOR=0.54, p=0.043). However, psychosocial needs were greater during the treatment (aOR=2.75, p=0.004) and recurrence phases (aOR=7.61, p=0.001).Conclusion: The unmet needs of lung cancer patients vary based on demographic characteristics and disease-related factors. Patients in the newly diagnosed phase have significantly higher unmet needs compared to other stages. Therefore, Healthcare professionals should provide appropriate and timely individualized care to address these needs.Keywords: unmet care needs, lung cancer, survivor, cancer stages and treatment